Short and Long Term Effects of High-Intensity Interval Training on Hormones, Metabolites, Antioxidant System, Glycogen Concentration, and Aerobic Performance Adaptations in Rats - de Araujo, Gustavo G.; Papoti, Marcelo; dos Reis, Ivan Gustavo Masselli; de Mello, Maria A. R.; Gobatto, Claudio A. (Frontiers in Physiology, 2016)
The purpose of the study was to investigate the effects of short and long term High-Intensity Interval Training (HIIT) on anaerobic and aerobic performance, creatinine, uric acid, urea, creatine kinase, lactate dehydrogenase, catalase, superoxide dismutase, testosterone, corticosterone and glycogen concentration (liver, soleus and gastrocnemius). The Wistar were separated in two groups: HIIT and sedentary/control (CT). The lactate minimum (LM) was used to evaluate the aerobic and anaerobic performance (AP) (baseline, 6 and 12 wk). The lactate peak determination consisted of two swim bouts at 13% of body weight (bw): 1) 30 s of effort; 2) 30 s of passive recovery; 3) exercise until exhaustion (AP). Tethered loads equivalent to 3.5, 4.0, 4.5, 5.0, 5.5 and 6.5% bw were performed in incremental phase. The aerobic capacity in HIIT group increased after 12 wk (5.2±0.2 % bw) in relation to baseline (4.4±0.2 % bw), but not after 6 wk (4.5±0.3 % bw). The exhaustion time in HIIT group showed higher values than CT after 6 (HIIT= 58±5 s; CT=40±7 s) and 12 wk (HIIT=62±7 s; CT=49±3 s). Glycogen (mg/100mg) increased in gastrocnemius for HIIT group after 6 wk (0.757±0.076) and 12 wk (1.014±0.157) in comparison to baseline (0.358±0.024). In soleus, the HIIT increased glycogen after 6 wk (0.738±0.057) and 12 wk (0.709±0.085) in comparison to baseline (0.417±0.035). The glycogen in liver increased after HIIT 12 wk (4.079±0.319) in relation to baseline (2.400±0.416). The corticosterone (ng/mL) in HIIT increased after 6 wk (529.0±30.5) and reduced after 12 wk (153.6±14.5) in comparison to baseline (370.0±18.3). In conclusion, long term HIIT enhanced the aerobic capacity, but short term (6wk) was not enough to cause aerobic adaptations. The anaerobic performance increased in HIIT short and long term compared with CT, without differences between HIIT short and long term. Furthermore, the glycogen super-compensantion increased after short and long term HIIT in comparison to baseline and CT group. The corticosterone increased after 6 wk, but reduces after 12 wk. No significant alterations were observed in urea, uric acid, testosterone, catalase, superoxide dismutase, sulfhydryl groups and creatine kinase in HIIT group in relation to baseline and CT.